2014
DOI: 10.1007/s00265-014-1730-y
|View full text |Cite
|
Sign up to set email alerts
|

Female-female competition is influenced by forehead patch expression in pied flycatcher females

Abstract: 24There is increasing evidence that sexual selection operates in females and not only in males. 25However, the function of female signals in intrasexual competition has been little studied in 26 species with conventional sex roles. In the Iberian populations of the pied flycatcher (Ficedula 27 hypoleuca), some females express a white forehead patch, a trait that in other European 28 populations only males exhibit and has become a classical example in studies of sexual 29 selection. Here, we investigated whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…Thus, males may affect female territorial behaviour through their capacity to exclude intruding males (Kellam et al 2006;Moreno et al 2013). Accordingly, it has been shown that male absence may increase female aggressiveness, suggesting that females take on extra costs of territoriality when their mates are not present (Morales et al 2014). More dominant males are expected to exclude male intruders more efficiently, and this could positively affect female physiological state (Moreno et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, males may affect female territorial behaviour through their capacity to exclude intruding males (Kellam et al 2006;Moreno et al 2013). Accordingly, it has been shown that male absence may increase female aggressiveness, suggesting that females take on extra costs of territoriality when their mates are not present (Morales et al 2014). More dominant males are expected to exclude male intruders more efficiently, and this could positively affect female physiological state (Moreno et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Social selection (defined in West-Eberhard, 1979) focuses on the role of social interactions as drivers of selection, regardless of whether the interaction is sexual or non-sexual Tobias et al, 2012). Although still not widely embraced and somewhat controversial, social selection predicts that the strength of social interactions may determine how aggressive traits such as vocalizations, coloration, weapons, and ornaments correlate with measures of reproductive success (McComb et al, 1994;Friedman et al, 2009;Cornwallis and Uller, 2010;Santana et al, 2012;Tobias et al, 2012;Morales et al, 2014).…”
Section: Female Song and Social Selectionmentioning
confidence: 99%
“…Although studies have demonstrated that such traits function as signals of quality that are preferred by males (Griggio et al, 2005;Torres and Velando, 2005) and are important in agonistic interactions (Griggio et al, 2010;Midamegbe et al, 2011;Morales et al, 2014), Ornamental traits of females that are preferred by males may influence their investment in reproduction (Edward, 2015). For instance, variation in the attractiveness of ornamentation displayed by females may influence how much parental care males invest in the current reproductive attempt (Burley, 1986;Sheldon, 2000).…”
Section: Chapter 7: Synthesismentioning
confidence: 99%
“…In line with this, Moreno et al (2013) reported that non-ornamented female pied flycatchers manipulated to display a forehead patch had higher oxidative damage compared to control females and hypothesized that competition for limited nest sites may enforce the honesty of female ornamentation. Territorial defence by resident female birds toward decoy intruders is strongly influenced by the ornamentation of both the resident and intruding female (Midamegbe et al, 2013;Morales et al, 2014), which may suggest that nest site intrusions by conspecific females provides a mechanism to enforce the honesty of quality signals, but to my knowledge this has never been experimentally tested in free-living female birds.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation